A Survey of the Practice of After-Hours and Emergency Endoscopy in Canada. (2012) - Muthiah, Karuppan Chetty; Enns, Robert; Armstrong, David; Noble, Angela; Gray, James; Sinclair, Paul; Colacino, Palma; Singh, Harminder
Abstract : OBJECTIVE: To determine staffing and practice patterns for after-hours endoscopy service in Canada METHODS: A link to a web-based survey was sent by e-mail to all clinical members of the Canadian Association of Gastroenterology in February 2011. A priori, it was planned to compare variations in practice among gastroenterologists (GIs) performing endoscopy in different regions of Canada, between pediatric and adult GIs, and between university and community hospitals. RESULTS: Of 422 potential respondents, 168 (40%) responded. Of the 139 adult GIs, 61% performed after-hours endoscopy in the endoscopy suite where daytime procedures were performed, 62% had a trained endoscopy nurse available for all procedures, 38% had access to propofol sedation, 12% reprocessed the endoscopes themselves or with the help of a resident, 4% had out-of-hospital patients come directly to their endoscopy suite and 53% were highly satisfied. The adult endoscopists practising at community hospitals were more likely to have an anesthetist attend the procedure. Regional differences were noted, with more involvement of anesthetists (13%) and availability of propofol (50%) in Ontario, more frequent reprocessing of endoscopes in the central reprocessing units in British Columbia (78%) and almost universal availability of a trained endoscopy nurse (96%) with concomitant higher endoscopist satisfaction (84% highly satisfied) in Alberta. CONCLUSIONS: More than one-third of surveyed endoscopists across the country do not have a trained endoscopy nurse to assist in after-hours endoscopy – the time period when urgent patients often present and typically require therapeutic endoscopic interventions. There are significant regional differences in the practice of after-hours endoscopy in Canada.